KEPRIBADIAN TOKOH UTAMA DALAM NOVEL “HANA-TARA-HATA” KARYA TERE LIYE MELALUI PERSPEKTIF PSIKOANALISIS SIGMUND FREUD - Nike Risa Ayu Ningtyas; Nur Rohmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Modern life dynamics and complex social interactions influence human psychological development, including personality formation shaped by internal and external conflicts. Literary works serve as a medium for reflecting human psychological conditions, as portrayed in the novel Hana-Tara-Hata by Tere Liye, which depicts the psychological struggles of its main character in facing various life pressures. This study aims to describe the main character’s personality based on Sigmund Freud’s psychoanalytic theory, focusing on the elements of id, ego, and superego. This research uses a descriptive qualitative method with documentation techniques. The data consist of words, phrases, and sentences from the novel that represent personality aspects, analyzed using Freud’s psychoanalytic approach based on Alwisol’s Psychology of Personality. The primary data source is the novel Hana-Tara-Hata by Tere Liye, published by SabakGrip. The findings reveal that the id is represented through instinctive drives, basic desires, and impulsive actions based on the pleasure principle. The ego appears through realistic decision-making, self-control, and efforts to balance personal desires with external reality. Meanwhile, the superego is reflected through moral awareness, conscience, and adherence to internalized values that regulate behavior. The study concludes that Hana-Tara-Hata is not only a literary work but also a representation of human psychological dynamics, providing insight into personality development and individual behavior in real-life contexts.